The transcription factor FcMYB3 responds to 60Co γ-ray irradiation of axillary buds in Ficus carica L. by activating the expression of the NADPH oxidase, FcRbohD - Song, Miaoyu; Chen, Ziyu; Bahayiding, Wupur; Li, Jinping; Ma, Huiqin; Wang, Ziran (Frontiers in Plant Science, 2024)
Plant irradiation has been used to induce genetic variation in crop germplasm.However, the underlying mechanisms of plant responses to ionizing radiation stress are still unclear. In plants, reactive oxygen species (ROS) are produced with abiotic stress. Respiratory burst oxidative homologs (Rboh) genes are important regulators of plant ROS stress responses, but little is known of their involvement in the response to ionizing radiation stress. In this study, young branches of Ficus carica L. were irradiated with 60 Co γ-rays and axillary buds were collected after 3-48 h after irradiation. The differentially expressed genes (DEGs; p< 0.05) detected included an early (6 h) and sustained increase in member of the MAPK signaling pathway. The activities of superoxide dismutase SOD, POD and CAT in fig axillary buds showed a trend of first decrease and then increase with time, while the contents of MDA and H2O2 maintained an overall upward trend. The analysis of differentially expressed genes (DEGs; p < 0.05) indicated an early (6 h) and sustained increase in member of the MAPK signaling pathway. DEGs for glutathione-s-transferase and genes involved in phenylpropanoid and flavonoid biosynthesis pathways were detected at all time points, indicating that γ-irradiation induced an increased capacity for in ROSscavenging. Substantial changes in the expression of MYB, NAC and bHLH transcription factor family members were also seen to occur within 6 h after irradiation. Taking Rboh-derived ROS signaling pathway as the entry point, the MYB transcription factor, FcMYB3, was identified as an potential upstream regulator of FcRbohD in a yeast one hybrid assay and this interaction verified by LUC and EMSA experiments. The knock-down and overexpression of FcMYB3 indicated that FcMYB3 is a positive regulator of ROS accumulation in response to γ-ray radiation stress responses in fig. Our results will provide a better understanding of the mechanisms of radiation tolerance in plant materials.